Tourism carrying capacity, a tool for sustainable management in protected areas - Mestanza, Carlos; Sánchez Capa, Maritza Carolina; Gutiérrez, Mirian Jiménez (Tierra Infinita, 2019)
Carrying capacity has emerged as an important parameter to consider when developing a series of effective management tools for natural protected areas such that the experience of the average tourist remains satisfactory when exerting an "acceptable" or minimum impact to the protected area. The Cuyabeno Fauna Production Reserve (CFPR), one of the 56 protected areas of Ecuador. This is considered a good strategic place for hosting unique and representative ecosystems of the Amazon region. It is located in the provinces of Orellana and Sucumbios. This current research study determined the Tourist Carrying Capacity in the reserve´s publicly used paths, which will provide a management tool for managers to avoid environmental actions that could threaten conservation and sustainability. The Physical, Real and Effective Carrying Capacity was determined. In the determination of the Real Carrying Capacity (RCC), six factors of correction were considered: social, accessibility, erodibility, waterlogging, vegetation and wildlife. In the process of determining the Effective Carrying Capacity (ECC), the managers´ Capacity Management (CM) were considered. It was also determined that the saturation of the carrying capacity exists on the trails in the high season. The implementation of the local carrying capacity had lead not only to maintain the balanced use of resources at reserve but furthermore, combined with a other programs, to promote projects such as trail restoration, enhancing the relevance of the application of carrying capacity for the sustainable use of the areas of public use of the reserve.
Keywords: tourism; carrying capacity; satisfaction; protected areas